Behavioral Counseling with Systematic Desensitization Techniques to Reduce Anxiety : Development of Counseling Guidelines - Kartika Sari, Anak Agung Diah; Gading, I Ketut; Suranata, I Kadek (Bisma The Journal of Counseling, 2020)
This study aims to determine the acceptance (acceptedbillity) of behavioral counseling guides with systematic desensitization techniques to reduce student anxiety. This guide is an instrument for BK teachers in providing counseling guidance services in schools. The development procedure in this study follows the 4D development model which is limited only to content validation testing. There are five guidance and counseling experts and practitioners who have tested the feasibility of this guide. The instrument used for the assessment consisted of 25 items that referred to the acceptance of the handbook. Analysis of the results of the assessment uses the formulation of the content validity ratio calculation from Lawshe. The results of the analysis show that the validation of the cognitive behavioral counseling manual has a content validity index (CVI) of 0.95, which means very good or special. meet the eligibility criteria to be used as an instrument in carrying out counseling guidance services.